BANANA TRUNK: FROM FIBER TO PAPER - Indra Muis (JURNAL ADMINISTRASI KANTOR, 2015)
This article elaborate a social innovation practice made by a small group of people in Bandung West Java. The idea of this innovation is to use banana trunk as raw material for paper making. This article explains the manufacturing process of paper making by using banana trunks as raw material. Implementing a simple process, firstly the trunks are chopped into pieces. Next the pieces are dried under the sunshine. The dried pieces are then boiled. the next step is to blend the boiled pieces to make them jelly. the jelly is shaped in wood plates to make papers in the desired form and size. The plate are sunbathed to dry the jelly. The dried jelly now becomes papers.